2021
DOI: 10.1007/s10936-021-09784-1
|View full text |Cite
|
Sign up to set email alerts
|

No Self Without Salience: Affective and Self-relevance Ratings of 552 Emotionally Valenced and Neutral Dutch Words

Abstract: It is unknown how self-relevance is dependent on emotional salience. Emotional salience encompasses an individual's degree of attraction or aversion to emotionally-valenced information. The current study investigated the interconnection between self and salience through the evaluation of emotional valence and self-relevance. 56 native Dutch participants completed a questionnaire assessing valence, intensity, and self-relevance of 552 Dutch nouns and verbs. One-way repeated-measures ANCOVA investigated the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The present study is part of the Dutch Neuroimaging Dissociative Identity Disorder project that included the study of autobiographical memory. Participants information has been described in detail (Chalavi, Vissia, Giesen, Nijenhuis, Draijer, Barker, et al., 2015; Chalavi, Vissia, Giesen, Nijenhuis, Draijer, Cole, et al., 2015; Dimitrova et al., 2022; Vissia et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study is part of the Dutch Neuroimaging Dissociative Identity Disorder project that included the study of autobiographical memory. Participants information has been described in detail (Chalavi, Vissia, Giesen, Nijenhuis, Draijer, Barker, et al., 2015; Chalavi, Vissia, Giesen, Nijenhuis, Draijer, Cole, et al., 2015; Dimitrova et al., 2022; Vissia et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…All participants were female (only female individuals with DID volunteered), of Western European ancestry, native speakers of Dutch, and aged between 18 and 65 years. Notably, a word rating pilot study conducted in an independent healthy control group showed that emotional and self‐relevance processing is gender independent (Dimitrova et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations